Barriers to Pursuing Dream Jobs for People with Disabilities – From Their Perspective - Pałgan, Bartek (Niepełnosprawność i praca: Wymiary, konteksty, perspektywy, 2024)
The article will be based on research conducted using autoethnographic method, through free interviews with individuals with disabilities seeking employment, as well as recruiters and job inter-mediaries from various foundations and associations who professionally engage in job search and support for people with disabilities. The primary methodology will also include participant observation of this phenomenon. The aim of this study is to show individuals with disabilities that sometimes it’s enough to be willing to explore alternative solutions without being solely attached to what they already know. This is especially relevant for individuals with acquired disabilities, who, due to certain types of work, may no longer be able to return to their previous tasks, e.g., as a result of post-traumatic injuries. In such cases, this paper will demonstrate to these individuals that they should not despair by focusing solely on one job, but rather seek other possibilities, expand their skills and horizons. In addition to personal observations, interviews with employees of various foundations or associations offering developmental programs are crucial in this context.It is often said that a potential employer would prefer to hire a fully abled person with subsidies for their work, as is the case with hiring a person with disabilities. Through this article, the author aims to challenge these words because for not all employers, which may seem surprising, this is the most important factor. It is worth noting, based on the author’s professional experience, that not all employers know how to take advantage of these incentives, and some, as research has shown, do not focus on this and even idealistically employ such individuals to help them, simply focusing on the competencies possessed by these individuals rather than subsidies. Of course, we are talking here about a small number of such employers, but it is important to emphasize that such employers also exist.